PERENCANAAN PARTISIPATIF DESA TAMBUSAI BATANG DUI KECAMATAN MANDAU PASCA PEMEKARAN TAHUN 2015 - Khairani, Sarah; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Planning is a requirement for the implementation of good development, which the involvement of the society is very important in development planning in order the result of the policy will be appropriate on target. Development planning is arranged participatoryly is a plan that involve the society. Deliberation of development planning is one of public vehicle to optimize the utilization of society participation in the planning arrangement. However, in the process of participatory planning there are several phenomena namely the implementation of development Tambusai Batang Dui Village is not in accordance with existing planning and development is not in accordance with the standards of eligibility has been established.The purpose of the research is first to know the participatory planning of Tambusai Batang Dui Village and also the factors influencing the participatory planning. This research uses the theory of Participatory Planning. The approach used in this research is qualitative approach. Type of research data is primary data and secondary data. Technique of collecting data in this research is documentation, interview, and questionnaire. Analysis technical of data used is descriptive qualitative data analysis.The results of this study indicate that the participatory planning process is less than the maximum can be seen from the participatory planning processes Tambusai Batang Dui Village are investigation, formularization problem, support identification from the society , the purpose formularization, detailed steps, and designing budgets that are not fully participatory. There are several factors that influence the participation of the society, namely awareness and willingness of society, education, income, leadership of village government and facilities.Keywords: planning, participatory planning